Can You Joke about Anything? Freedom of Speech, Entitlement and Context in Humour - Liliequist, Christian (Nordlit, 2023)
In this article, humour about sensitive and taboo subjects is analyzed from three perspectives: freedom of speech, entitlement, and context. Freedom of speech, in the form of the right to joke about anything, can be seen as an important principle in humour discourses. In debates about humour, it is common to refer to freedom of speech in defense of what has been criticized. In my empirical material, however, a principle of entitlement is also articulated that concerns what kind of jokes you have the right to tell depending on who you are. The principle of entitlement contravenes the principle of freedom of speech. Finally, the context of a joke is also important for what you can joke about. When a comical expression is recorded and spread through social media and/or streaming services to another audience than that it was originally meant for, there is a risk that some individuals and/or groups in society will interpret it in another way and perceive it as offensive.
Keywords: Humour; stand-up comedy; taboo; freedom of speech; entitlement; context